Electrical conductivity and capacitance spectra of Bi1.37Sm0.13Zn0.92Nb1.50O6.92 pyrochlore ceramic in the range of 0-3 GHz - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2014)
In this work, the electrical properties of samarium-doped bismuth niobium zinc oxide (Sm-doped BZN) pyrochlore ceramics are investigated by means of temperature dependent electrical conductivity and capacitance spectroscopy in the frequency range of 0-3 GHz. It was observed that the novel dielectric Sm-BZN ceramic exhibits a temperature and electric field dependent dielectric breakdown. When measured at 300 K, the breakdown electric field is 1.12 kV/cm and when heated the breakdown temperature is similar to 420 K. The pyrochlore is thermally active above 440K with conductivity activation energy of 1.37 eV. In addition, the room temperature capacitance spectra reflected a resonance-antiresonance switching property at 53MHz when subjected to an AC signal of low power of 5 dBm. Furthermore, when the Sm-BZN ceramics are used as microwave cavity and tested in the frequency range of 1.0-3.0 GHz, the cavity behaves as low pass filter with wide tunability up to a frequency of 1.91 GHz. At this frequency it behaves as a band rejection filter that blocks waves of 1.91 GHz and 2.57 GHz frequencies. These properties of the Sm-doped BZN are promising as they indicate the usability of the ceramics in digital electronic circuits as resonant microwave cavities suitable for the production of low pass/rejection band filters.
Keywords: Samarium doping; electrical resistivity; microwave cavity; THIN-FILMS; DIELECTRIC-PROPERTIES